Evaluation of OSMOCELLS, a new semi‐automatic device for osmotic fragility assessment. (8th May 2017) - Gérard, D.; Fattet, A‐J.; Brakta, C.; Phulpin, A.; Steschenko, D.; Lesesve, J‐F.; Perrin, J.
Summary: Introduction: The osmotic fragility (OF) test was a central test for the diagnosis of hereditary red blood cell (RBC) disorders (mostly hereditary spherocytosis (HS), but thalassaemia as well). Nowadays although the traditional multitubes method has lost a prominent place, many laboratories still perform such a laboured test, despite the lack of standardization. In fact, the evaluation of OF may offer an inexpensive screening for RBC disorders. We present a new semi‐automatic device, allowing the continuous recording of OF, by an updated dialysis method. Methods: Repeatability, stability over time, influence of the anticoagulant were evaluated among a population of healthy blood donors. The test was then performed among patients presenting inherited RBC disorders (HS or haemoglobinopathies) where OF is typically altered. Results: Repeatability was excellent; the parameters were greatly influenced by the nature of the anticoagulant and interestingly appeared stable for 48 h. Patients with RBC disorders displayed the expected profile in regard with their disease: patients with HS all presented an increased OF while patients with haemoglobinopathy displayed resistant profiles. Conclusion: The device offers a substantial improvement in terms of standardization and consistency of the results and may offer a considerable gain for general laboratories.